Exploring Parents' Perceptions Regarding the Importance of Scientific Literacy as a Consideration in Choosing an Elementary School - Siti Komariah; Muhammad Zuhaery; Suyatno Suyatno (Postgraduate, University of Mataram, 2026)
Basic education is a crucial foundation for a child's academic journey. Amidst the dynamics of the 21st century, dominated by technological advancements and global challenges—from climate change to health crises—the ability to understand and apply scientific concepts is vital. Scientific literacy is not simply the ability to memorize formulas or the names of planets, but rather the capacity to think critically, evaluate evidence-based information, and make logical decisions in everyday life. Changes in parental preferences in choosing elementary schools in Sungai Seluang Village are important to study because they indicate a trend of increasing interest in private schools compared to public schools, in line with the national trend of decreasing public school enrollment. This study primarily aims to examine factors influencing parental decisions, including comparing views on the quality of public and private schools, identifying barriers to accessing information, and assessing the influence of school location. The method used is a qualitative approach (case study) with data collection through interviews, observation, and documentation, then analyzed through data reduction, data presentation, and drawing conclusions, accompanied by triangulation for validity testing. The results show that the dominant factors influencing parental choices include teaching quality, facilities, access to information, perceptions of security, and school distance, and these findings are directed to support the development of more responsive local education policies.